2022
DOI: 10.1038/s41598-022-17600-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serotype prevalence of Streptococcus pneumoniae in Southampton, UK between 2006 and 2018

Abstract: Streptococcus pneumoniae continues to cause significant disease burden. Whilst pneumococcal conjugate vaccines (PCV) have substantially reduced this burden, serotype replacement partially negates this success due to increased disease associated with non-vaccine serotypes (NVTs). Continued surveillance is therefore essential to provide crucial epidemiological data. Annual cross-sectional surveillance of paediatric pneumococcal carriage was started in Southampton, UK following PCV7 roll-out in 2006. Nasopharynge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…1c ). This contrasts with other PCV7 and PCV13 serotypes that have decreased over the same period [ 40 ]. For IPD the proportion of serotype 3 ranged from 0 % (all periods between 2008/09 and 2011/12) to a maximum of 16.7 % (average: 6.6 %) ( Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…1c ). This contrasts with other PCV7 and PCV13 serotypes that have decreased over the same period [ 40 ]. For IPD the proportion of serotype 3 ranged from 0 % (all periods between 2008/09 and 2011/12) to a maximum of 16.7 % (average: 6.6 %) ( Fig.…”
Section: Resultsmentioning
confidence: 90%
“…On average the proportion of serotype 3 observed in carriage has remained relatively steady at 1.4 %, ranging from 0 to 3.9 %, which was observed in the 2011/12 winter period (). This contrasts with other PCV7 and PCV13 serotypes that have decreased over the same period [40]. For IPD the proportion of serotype 3 ranged from 0 % (all periods between 2008/09 and 2011/12) to a maximum of 16.7 % (average: 6.6 %) ().…”
Section: Resultsmentioning
confidence: 94%
“…and UK IPD surveillance data further demonstrated that PCV13 achieved near elimination of matched PCV7 serotypes over its decade of use. 40,41 Notably, a 3-dose series was recommended in Israel and UK at PCV13 introduction. 42,43 Assessment of various immune responses for PCVs is important because the mechanism of protection of PCVs against pneumococcal disease is multifactorial, and no minimum circulating IgG level predicting protection is established.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of pneumococcal conjugate vaccine (PCV), PCV13 in 2010 had a significant impact on serotype prevalence. The study found that proportion of PCV13 serotypes decreased, while non-PCV13 serotypes increased over time [ 9 ]. Recent study in Urumqi, China analyzed the serotype distribution and drug resistance of S. pneumoniae in children aged 8 years and under between 2010 and 2021.…”
Section: Introductionmentioning
confidence: 99%